Endoscopic Treatment and Prevention of Acute Variceal Hemorrhage - Youngdae Kim (Yong Chan Lee, 2024)
Gastroesophageal varices occur in more than half of patients with cirrhosis and the incidence increases as liver function worsens. Although the mortality rate for acute variceal bleeding has decreased with the development of variceal endoscopic hemostasis and administration of vasoactive drugs and prophylactic antibiotics, it still reaches 20%. Therefore, surveillance of variceal occurrence and the prevention of their bleeding is very important in patients with cirrhosis. In patients with liver cirrhosis accompanied by portal hypertension, esophagogastroduodenoscopy should be performed to diagnose varices and stratify their bleeding risk. The interval of endoscopic surveillance is adjusted according to variceal condition and cirrhosis severity. If varices are diagnosed, primary prophylaxis (e.g., non-selective beta-blockers or endoscopic prophylaxis) is required to prevent variceal bleeding. Appropriate treatment, including timely endoscopic hemostasis, should be performed in patients with acute variceal bleeding, and secondary prophylaxis is required to prevent rebleeding. Endoscopic variceal ligation is the recommended endoscopic treatment for acute esophageal variceal bleeding; endoscopic variceal obstruction is usually recommended in patients with gastric varices. To prevent bleeding, endoscopic surveillance should be performed at regular intervals until the varices have been eradicated, and endoscopic followup should be performed periodically even after their disappearance. In this review, we investigate the role of endoscopy in the treatment and management of gastroesophageal varices.